Screw Conveyor Design to Reduce Musculoskeletal Disorders (MSDs) Risk in Coconut Shell Handling - Fajar Hadi Crisnamurti; Agus Edy Pramono (MBI, 2025)
This study aims to analyze the working posture of operators involved in feeding coconut shells into a processing machine, using the Rapid Entire Body Assessment (REBA) method. The assessment yielded a total REBA score of 9, which indicates a high level of ergonomic risk requiring immediate corrective action. This elevated score is attributed to repetitive movements during the material handling process. To mitigate the risk of Musculoskeletal Disorders (MSDs), a specially designed portable screw conveyor is proposed as an assistive tool. The proposed conveyor is expected to significantly reduce physical strain and improve the overall ergonomics of the task. Visual illustrations of the design and technical drawing are provided to support the implementation concept. This study highlights the importance of ergonomic interventions in industrial settings to promote worker health and operational efficiency.